2009
DOI: 10.1108/17410390910922804
|View full text |Cite
|
Sign up to set email alerts
|

A benefits realisation road‐map framework for ERP usage in small and medium‐sized enterprises

Abstract: PurposeThe purpose of this paper is to develop a benefits realisation road‐map for ERP usage in the context of small and medium‐sized enterprises (SMEs).Design/methodology/approachDirect interviews were used to collect data from a random sample of 48 MBA students and 87 business managers (CIO/IT directors and CFO roles).FindingsThe ERP benefits road‐map suggests that a long‐term vision is required in order to obtain a successful realisation of the potential benefits that ERP could bring. Thus, this analysis su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 13 publications
1
90
0
5
Order By: Relevance
“…There is a growing body of literature that advances the case for a variety of different benefits realisation tools, techniques and approaches [e.g. Reymeni & SherwoodSmith, 1999;Ward & Daniel, 2006;Bradley, 2006;Esteves, 2009]. However, there has been relatively little empirical investigation of what, if anything, organisations are doing in practice, to proactively manage benefits from their IT investments.…”
Section: Benefits Driven Approaches To Systems Developmentmentioning
confidence: 99%
“…There is a growing body of literature that advances the case for a variety of different benefits realisation tools, techniques and approaches [e.g. Reymeni & SherwoodSmith, 1999;Ward & Daniel, 2006;Bradley, 2006;Esteves, 2009]. However, there has been relatively little empirical investigation of what, if anything, organisations are doing in practice, to proactively manage benefits from their IT investments.…”
Section: Benefits Driven Approaches To Systems Developmentmentioning
confidence: 99%
“…Esteves (2009) attribute this trajectory to the fact that a majority of manufacturing SMEs are still in the lower stages of adoption as these firms perceive very low levels of supply chain benefits from e-business. However, Chan and Swatman (2000) found that technology intensive industries have reaped the rewards of Internet technology which are yet to be experienced by traditional marketers.…”
Section: The Sme Sector and Its Importancementioning
confidence: 99%
“…They observed that some business benefits were achieved in the companies that implement the ERP system. To realize the full benefits, Esteves (2009) noted that the achievement of ERP benefits requires a long-term vision. Jahangir et al (2007) suggested that a combination of both technology and organizational factors produces higher process outcomes (i.e., process efficiency, effectiveness, and flexibility) by focusing on ERP implementations.…”
Section: Studies On the Support Of Business Processes Rolementioning
confidence: 99%